Bioinformatics identification of key genes and therapeutic targets for exercise intervention in polycystic ovary syndrome - Yang, Xiaodie; Yang, Hong; Shen, Dongyi; Zhang, Qiang; Zhu, Chan (Frontiers in Genetics, 2025)
Background and PurposeWe aimed to explore the mechanisms and pathways of exercise-based interventions in the treatment of polycystic ovarian syndrome (PCOS).MethodsIn this literature review, studies related to exercise therapy for PCOS that were published in the past 20 years were searched, potentially effective active ingredients were screened, and gene prediction of active ingredients and diseases was conducted using the compound and GeneCards databases, respectively, to identify potential targets of exercised-related bioactive molecules in PCOS. Finally, hub genes and signaling pathways were predicted using bioinformatic methods.ResultsThe review identified eight potential effective components were screened out, including irisin, 5α-reductase, kisspeptin, cocaine-and amphetamine-regulated transcript, nerve growth factor, nerve peptide Y, insulin-like growth factor-1, and interleukin-6. A total of 192 target genes for exercise-related components and PCOS were identified, including the hub genes TNF, IL6, IL1B, JUN, CCND1, and PSMA7.ConclusionThe hub genes identified in this review indicate that exercise therapy in PCOS may affect the protease system, renin–angiotensin system, inflammatory signal transduction, neuroactive ligand–receptor interaction, and other pathways through the G protein-coupled receptor signaling pathway, neuropeptide signaling pathway, endocrine process, and other biological processes and regulate apoptosis, cell cycle, and intercellular communication.